Cover Image. (20th March 2017) - Rostamnia, Sadegh; Jafari, Maryam
Abstract : The cover image, by Sadegh Rostamnia et al., is based on the Full Paper Metal – organic framework of amine ‐ MIL ‐ 53 ( Al ) as active and reusable liquid ‐ phase reaction inductor for multicomponent condensation of Ugi ‐ type reactions, DOI10.1002/aoc.3584 .